Screening asymptomatic school children for early asthma by determining airway narrowing through peak expiratory flow rate measurement - Bharati Mehta; Bharti Bhandari; Anish Singhal; Manisha Mavai; Naveen Dutt; Pankaja Raghav (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Peak expiratory flow rate (PEFR) is widely used as a predictor of treatment of asthma patients. Peak expiratory flow and forced expiratory volume in first second (FEV1) are the most useful parameters for the diagnosis of asthma. Spirometry is not often available in the primary care setting, and economic factors may limit its testing. Mild airway narrowing may be present in asymptomatic children, which can be identified by determining their PEFR. This will enable us to initiate early treatment. MATERIALS AND METHODS: We selected 200 asymptomatic children at the age of 10-15 years without a history of smoking, tuberculosis, or other respiratory illness. A family history about asthmatic symptoms was sought. PEFR values of all children were recorded, and 40 children showed PEFR values less than 80% of their predicted values. To confirm whether the low observed values were because of airway obstruction, their spirometry was performed. RESULTS: Nine out of 47 (19.14%) children from asthmatic families and 31 out of 153 (20.26%) from nonasthmatic families showed PEFR values <80% of the predicted value (P > 0.05). Considering a decrease in the FEV1/forced vital capacity (FVC) ratio to <80% for the diagnosis of obstructive disease, only two out of 35 children were found to have it. Correlation between PEFR and FEV1/FVC ratio was not significant (r = 0.314 and P = 0.065). CONCLUSIONS: Asymptomatic children with low PEFR values may not show abnormal lung functions on spirometry. However, these children, particularly those having the risk of family history of asthma, may be followed for the development of airway obstruction.